Spinal hypermobility accelerates ossification in posterior longitudinal ligaments: insights from an in vivo mouse model - Tao Tang; Tao Tang; Zhengya Zhu; Zhengya Zhu; Zhongyuan He; Zhongyuan He; Fuan Wang; Lin Chen; Jianfeng Li; Hongkun Chen; Jiaxiang Zhou; Jianmin Wang; et al. (Frontiers in Physiology)
IntroductionOssification of the posterior longitudinal ligaments (OPLL) is characterized by heterotopic ossification in the posterior longitudinal ligament of spine. Our earlier research found that mechanical stimulation enhances osteogenic differentiation in OPLL-derived ligament cells. Nevertheless, the function of hypermobility of the spine on ligament ossification remain unexplored in vivo.MethodsWe created the novel stimulation device to induce spinal hypermobility in mice with heterotopic ossification of the spine ligaments. The mice were randomly divided into three groups, control, slow hypermobility (SH) group and fast hypermobility (FH) group according to the frequency of spinal movement. Ligament ossification and changes in spinal range of motion (ROM) were assessed using micro-CT and X-rays. Morphological alterations were examined through HE staining. Behavioral evaluation was performed using the Basso Mouse Scale (BMS) score and inclined plane test (IPT). Immunofluorescence was employed to examine the expression of related proteins.ResultsAfter 8 weeks, it showed increased ligament ossification and chondrocyte proliferation both in SH and FH group. After 16 weeks, The BMS score and IPT were lower both in the SH and FH group compared to the controls. Additionally, the ROM of cervicothoracic and thoracolumbar spine was lower in the FH group than in the controls. Immunofluorescence analysis revealed increased levels of SP7, RUNX2, OCN, DLX5, NOTCH1, and HES1 in the ligament tissues of the FH group compared to controls.Conclusionspinal hypermobility promotes the progression of ossification in mice with heterotopic ossification of the spine, shedding new light on the pathogenesis of OPLL.